Transformational Leadership to Build Productive Teacher Work Culture - Yuliyanti, Aida; Egar, Ngasbun; Nugroho, Aryo Andri (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
A productive teacher work culture is a key factor in improving the quality of learning and overall school performance. However, many schools still face challenges such as low discipline, limited collaboration, and a lack of innovation among teachers. This study aims to analyze the principal’s transformational leadership in building a productive teacher work culture at SD Muhammadiyah Sukorejo, Kendal Regency. This research employs a qualitative approach with a case study design conducted from October 2025 to March 2026. The research subjects consisted of one principal, one vice principal, three teachers, and six students selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using data reduction, data display, and verification techniques. The findings reveal that the principal’s transformational leadership is effectively implemented through four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The principal demonstrates strong role modeling through discipline, integrity, and Islamic values, provides inspirational motivation through consistent communication of vision and collective goals, encourages innovation and professional development among teachers, and offers individualized support through mentoring and emotional guidance. These leadership practices successfully foster a productive teacher work culture characterized by discipline, responsibility, collaboration, creativity, and continuous improvement. This study concludes that transformational leadership plays a significant role in shaping a sustainable and value-based teacher work culture, particularly in faith-based primary schools. The integration of professional and Islamic values strengthens teacher commitment and enhances overall school performance.